2022
DOI: 10.4314/gjds.v19i1.4
|View full text |Cite
|
Sign up to set email alerts
|

Student housing investment strategies through location and building services. A study of privately-owned student housing around university campuses in Northern Ghana

Abstract: The study assesses the investment strategies private investors employ in student housing to remain viable by attracting students to the hostels with minimum impact of location on such decisions of students. The study used a mixed-methods approach involving surveys and interviews. The Hedonic Price Model through Multiple regression and ANOVA were used to analyse quantitative data, while qualitative data were analysed using themes. The study found a gradual rise in student housing rent with increasing distance f… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2024
2024
2024
2024

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 0 publications
0
1
0
Order By: Relevance
“…The study found that a reduction and irregular cleaning of rooms and dust in student housing contributed to higher weights that led to diseases such as diarrhea, skin rashes, fever and malaria in SWD across the study locations. The nature of the inbuilt toilet facility does not have effects compared to studies (Aziabah et al, 2022;Attakora-Amaniampong et al, 2021). A student with a disability indicated that this does not affect their sleep.…”
Section: Discussionmentioning
confidence: 94%
“…The study found that a reduction and irregular cleaning of rooms and dust in student housing contributed to higher weights that led to diseases such as diarrhea, skin rashes, fever and malaria in SWD across the study locations. The nature of the inbuilt toilet facility does not have effects compared to studies (Aziabah et al, 2022;Attakora-Amaniampong et al, 2021). A student with a disability indicated that this does not affect their sleep.…”
Section: Discussionmentioning
confidence: 94%